Cinema Edukasi: Program Pemutaran Film sebagai Media Penguatan Nilai Karakter Kebangsaan pada Anak - Muh. Herisman; Riskawati Riskawati (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Character education is the main foundation in shaping the personality and identity of the nation's children from an early age. This community service activity aims to strengthen national character values ​​through educational films that are engaging and appropriate for children. The program, titled Educational Cinema, uses the film Nussa: "Good is Easy" as a means of learning the moral values ​​and virtues of Pancasila in a simple and enjoyable way. The activity was carried out at Wildanun Kindergarten, Makassar, involving 16 children. The activity was carried out in three stages: preparation, implementation, and reflection. The results of the activity showed an increase in children's understanding of national character values ​​such as religiosity, hard work, curiosity, love of the environment, appreciation of achievement, and social care. Teachers gained new experience in utilizing film media as a learning tool for Pancasila values. This program proves that digital media can be an effective means of instilling national character in the modern era.